IMPROVING STUDENTS' WRITING SKILLS IN RECOUNT TEXT USING TEACHING MEDIA PICTURES AND LEARNING INTERESTS - E. Laela Komala Susilawati (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This experimental study aims to determine the effects of teaching media and learning interest on students' writing skills in recount text. The sample of the research is 80 respondents. The technique of collecting data of each variable was acquired from the test. The data were analyzed using a two-way analysis of variance (ANOVA 2x2). The research shows that: 1) there is a significant effect of teaching media towards students writing skills in recount text at State Senior High School in Pandeglang Regency. It is proved by the value Sig 0,000 < 0,05 and Fo = 87,444; 2) there is a significant effect of learning interest towards students writing skill in recount text at State Senior High School in Pandeglang Regency. It is proved by the value Sig 0, 000 < 0,05 and Fo = 46,751; 3) there are no significant interactive effects of teaching media and learning interest towards students' writing skills in recount text at state senior high school in Pandeglang Regency. It is proved by the value Sig 0,05 or 0,380 > 0,05 and Fo = 0,778.Keywords: teaching media, learning interest, writing skills, recount text.